(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2022)
The main aim of the research is a diagnosis of attitudes to religion and religious institutions (their role in the public sphere of social functioning, and establishing high principles) and value system. Surveys were conducted in 2003 (a sample of 325 students), in 2008 (a sample of 379 students), and 2013 (a sample of 368 students). It was assumed that there are differences between this three groups in acceptance of attitudes and that attitudes depend on a value system. The theoretical ground was based upon Rokeach’s concept, and The Value Survey of this author was used. A designated tool was constructed to measure attitudes. The results of research allow to state that approximately a half of the students expose significance of religion and religious institutions in public life, and identify religion as an important source of high principles. The attitudes were accepted by a smaller percentage of respondents in the third wave in comparison to the first and the second wave. Moreover, the attitudes were connected with a particular pattern of a value system that indicates differentiation of individualism – collectivism dimension.